Implementation of Legal Theory by Notary in Exercise Its Authority - Mochammed Dzakhy Ariefuddin Dwi Putranda; Wahyu Adhi Admaja; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To find out what a notary authority. 2) To determine and analyze the correlation between the Notary Law Theory to exercise its authority.Based on the results of data analysis concluded that: 1) Based on the duties and authority of Notary asserted in UUJN, split into three areas of authority ie general authority (Article 15 paragraph 1 UUJN), a special authority (Article 15 paragraph 2 UUJN), the authority which is to be determined (Article 15, paragraph 3 UUJN), 2) Conditions Referring to the basic acquisition of authority, that the notary in a deed relating to land comes from legislation that is under the authority attribution means authorizing the new government by a provision in the legislation which in this case is Notary Law, so authority obtained through the attribution is a genuine authority.Keywords: Theory of Law; Notary; Authorities.